2021
DOI: 10.1016/j.jbc.2021.101146
|View full text |Cite
|
Sign up to set email alerts
|

Human DIMT1 generates N26,6A-dimethylation–containing small RNAs

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…However, our results suggest that certain cell types such as AML cells are more sensitive to DIMT1 deficiency (Figure 1A). In our previous study (Shen et al 2021), we observed that DIMT1 +/-HEK 293T expressing E85A-DIMT1 has reduced translation and cell proliferation compared to DIMT1 +/-HEK 293T expressing the WT-DIMT1. But E85A DIMT1-expressing MOLM-13C cells have indistinguishable cell proliferation from WT-DIMT1 cells.…”
Section: The Rrna Cleft Identified In This Study Is An Achilles' Heel...mentioning
confidence: 83%
See 3 more Smart Citations
“…However, our results suggest that certain cell types such as AML cells are more sensitive to DIMT1 deficiency (Figure 1A). In our previous study (Shen et al 2021), we observed that DIMT1 +/-HEK 293T expressing E85A-DIMT1 has reduced translation and cell proliferation compared to DIMT1 +/-HEK 293T expressing the WT-DIMT1. But E85A DIMT1-expressing MOLM-13C cells have indistinguishable cell proliferation from WT-DIMT1 cells.…”
Section: The Rrna Cleft Identified In This Study Is An Achilles' Heel...mentioning
confidence: 83%
“…Previous studies have suggested that DIMT1 is highly expressed in leukemia cells (Shen et al 2021) (https://depmap.org/portal/publications/). CERES score showed moderately higher dependency of leukemia cells on DIMT1 gene compare to all cancers (Supplementary Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dimethyladenosine transferase 1 (dimt1), a conserved RNA methyltransferase (m26,6a), is crucial in ribosome biogenesis, cell viability, and protein synthesis. Dimt1 can also interact with miR-7132a, reflecting the possible connection and potential interaction between them (Shen et al, 2021). Besides, euchromatic histone lysine methyltransferase 2 (Ehmt2/G9a) (Ryu et al, 2022), and Lysine-specific demethylase 2A (KDM2A), (Xu et al, 2019), play important roles in a variety of cancers through regulation in multiple immune-related pathways.…”
Section: Functional Dmrs Related Genes Potentially Interacted With Demsmentioning
confidence: 99%